Language, culture and identity : an ethnolinguistic perspective - Riley, Philip (Advances in sociolinguistics., 2007)
How language shapes and is shaped by identity is a key topic within sociolinguistics. An individual's identity is constituted through a variety of different factors, including the social, linguistic, cultural and ethnic contexts. In this book, Philip Riley looks at these issues against the theoretical background of the sociology of knowledge, and ethnolinguistics, asking how we learn who we are and how social identities are negotiated. The idea of 'the foreigner' is central to this account, yet traditional views of the role of being socially 'other' largely neglect the role of language. Riley.